Pengolahan Kecap Jamur Tiram Menggunakan Enzim Bromelin di SMKN 7 Kota Bengkulu - Widawati, Lina; Azhari, Diah; Mujiono, Mujiono; Darius, Darius (Universitas Dehasen Bengkulu, 2024)
Oyster mushrooms have a high nutritional content, so they are often used as a base for dishes or snacks. Because of the high protein and glutamic acid content in oyster mushrooms, they have the opportunity to be processed into soy sauce. The use of bromelain enzyme from pineapple juice can produce oyster mushroom soy sauce with good quality characteristics. Oyster mushrooms provide dietary fiber and other ingredients that can improve health. Oyster mushroom is a very interesting prospect, because it is a commodity that has a fairly high quality demand. SMKN 7 Bengkulu City has an industrial and culinary department. The knowledge and skills of students on the progress of the oyster mushroom marketing business and its processed diversification results are still relatively underdeveloped. This is due to several factors including: lack of knowledge and skills in food processing, relatively small interest of students in the process of diversifying processed foodstuffs, and relatively small skills of students in extending shelf life and increasing the economic value of food products. Modern packaging and labeling, oyster mushroom soy sauce products using bromelain enzyme will become more economically valuable and feasible to develop and allow for expansion of the marketing area. Therefore, the community service team together with partners identified that it is necessary to improve soft skills and skills for students of SMKN 7 Bengkulu City, which can be done through training and applications in community service programs.